Phenotypic Differentiation of Purebred and Crossbred Indigenous Chicken Genotypes Using Multivariate Analysis - Venkatas, J.; Adeleke , M.A.; Peters, S.O.; Adebambo, O.A. (International Journal of Poultry Science, 2019)
Background and Objectives: Indigenous chickens serve as a good source of animal protein, particularly in developing countries. However, these birds have low reproduction and slow growth rate, which limits their commercial use. The growth performance of indigenous chickens can be improved through crossbreeding. This study utilized multivariate analysis to phenotypically characterize purebred and crossbred indigenous chicken genotypes. Materials and Methods: A total of 607 chickens were generated through artificial insemination. The parent stock involved indigenous Normal Feather, Naked Neck and Frizzle Feather chickens, along with a broiler breeder, Anak Titan. Weekly body weights (BWs) and linear body measurement data were collected from each bird from 1-day-old to 20 weeks of age. Data were then subjected to multivariate analysis. Results: Two principal components (PCs), PC1 and PC2 which ranged from 78.00-98.20% and from 0.71-10.90% of total variance, respectively, were generated. Discriminant analysis demonstrated a low level of morphometric differentiation among the chicken genotypes with six highly discriminating variables. Conclusion: Multivariate analysis allowed for differentiation of purebred and crossbred chicken genotypes based on morphometric traits. This result demonstrated the utility of multivariate analysis in making crossbreeding and selection decisions of indigenous chickens’ improvement.